Perbaikan Sistem Manajamen Gudang Bahan Baku PT. X - Ricardo Julian Adiputra; Iwan Halim Sahputra (Jurnal Titra, 2021)
PT. X is a private company engaged in the manufacture of weapons (Alutsista) the Main Equipment of the Indonesian National Army Weapon System. The company has had problems with warehouse management where the arrangement of raw materials on shelves that are placed arbitrarily, recording incoming and outgoing goods is still manual and also has problems with warehouse SOPs. In the raw material warehouse there are 7 shelves, each shelf consists of 3 stacks. By making changes to the warehouse layout, you can make your own warehouse activities more efficient. Then by applying the fixed storage method and labeling the identity on each shelf, the search and retrieval time of goods before is 37,092 seconds and after is 23,632 seconds. For changes to the SOP itself, the company previously had 3 SOPs and the new plan became 7 SOPs. The SOP itself is divided, merged and simplified the sentences from the old SOP to the new SOP. The use of Visual Basic for Applications for recording incoming and outgoing goods themselves to facilitate warehouse operators in carrying out the data collection process and also reduces the risk of incorrect data entry.